BRANDING STRATEGY DESIGN FOR TANGERANG'S OLD MARKET AREA TO INCREASE GLOBAL TOURISM ATTRACTIVENESS - Aliyah; Septi Mis Nurytussa'Diah; Aulya Nabila; Muhamad Reyhan Wiyanto (Journal Informatic, Education and Management (JIEM), 2026)
The Old Market area of ​​Tangerang is a tourist destination with high historical and multicultural value , but until now it has not had a structured branding strategy to reach global tourists . This study aims to design a branding strategy for the Old Market area of ​​Tangerang to increase its global tourist appeal . The method used is descriptive qualitative with a SWOT analysis approach (Strengths, Weaknesses, Opportunities, Threats), STP (Segmenting, Targeting, Positioning), and Brand Identity Prism (Kapferer). Data were obtained through field observations , interviews , and literature studies . The results of the study show that the Old Market has unique advantages in the form of Chinese - Muslim multicultural values , authentic culinary , and the Benteng Heritage Museum as an attraction . The SWOT analysis identified great opportunities from the growing global cultural tourism trend , where foreign tourist visits to Indonesia reached 11.68 million in 2023. Based on STP, the main target is cultural heritage tourists aged 25–45 years from East Asia and Western Europe . Brand Identity Prism produces a recommended brand persona "Tangerang Living Heritage" which emphasizes authenticity. , cultural diversity , and immersive tourist experiences . This strategy is expected to be able to position Pasar Lama as a highly competitive world - class cultural tourism destination .